Cognitive Outcomes After Transcatheter Aortic Valve Implantation: A Metaanalysis. Issue 2 (21st November 2017) - Khan, Maisha M.; Herrmann, Nathan; Gallagher, Damien; Gandell, Dov; Fremes, Stephen E.; Wijeysundera, Harindra C.; Radhakrishnan, Sam; Sun, Yue Ran; Lanctôt, Krista L.
Abstract : Objectives: To quantitatively summarize changes in cognitive performance in individuals with severe aortic stenosis undergoing transcatheter aortic valve implantation (TAVI). Design: Metaanalysis. Participants: Individuals undergoing TAVI (N = 1, 065 (48.5% male) from 18 studies, average age ≥80). Measurements: The MEDLINE, EMBASE, and Cochrane Central databases were searched for original peer‐reviewed reports assessing cognitive performance using standardized cognitive tests before and after TAVI. Data were extracted for cognitive scores before TAVI; perioperatively (within 7 days after TAVI); 1, 3, and 6 months after TAVI, and 12 to 34 months after TAVI (over the long term). Standardized mean differences (SMDs) were generated using random‐effects models for changes in cognition at each time point. Metaregression analyses were conducted to assess the association between population and procedural characteristics and cognitive outcomes. Risk of bias was assessed. Results: There were no significant changes from baseline in perioperative cognitive performance (SMD = 0.05, 95% confidence interval (CI) = −0.08–0.18; z = 0.75, P = .46), although overall cognitive performance had improved significantly 1 month after TAVI (SMD = −0.33, 95% CI = −0.50 to −0.16; z = 3.83, P < .001). There were no differences in cognitive performance 3 and 6 months after TAVI or over the long term. Cognitive outcomes were not associated with any covariates in regression analyses. Conclusion: Cognitive performance is preserved after TAVI, suggesting TAVI is not detrimental to cognition. Abstract : See related editorial byTalbot-Hamon et al .